Agonistic Autoantibodies to the Angiotensin II Type 1 Receptor Enhance Angiotensin II–Induced Renal Vascular Sensitivity and Reduce Renal Function During Pregnancy. Issue 5 (November 2016) - Cunningham, Mark W.; Williams, Jan M.; Amaral, Lorena; Usry, Nathan; Wallukat, Gerd; Dechend, Ralf; LaMarca, Babbette
Abstract : Preeclamptic women produce agonistic autoantibodies to the angiotensin II type 1 receptor (AT1-AA) and exhibit increased blood pressure (mean arterial pressure), vascular sensitivity to angiotensin II (ANG II), and display a decrease in renal function. The objective of this study was to examine the renal hemodynamic changes during pregnancy in the presence of AT1-AAs with or without a slow pressor dose of ANG II. In this study, mean arterial pressure was elevated in all pregnant rats treated with ANG II with or without AT1-AA. Glomerular filtration rate was reduced from 1.90±0.16 mL/min in normal pregnant (NP) to 1.20±0.08 in ANG II+AT1-AA rats. Renal blood flow was decreased in ANG II+AT1-AA versus NP rats to 7.4±1.09 versus 15.4±1.75 mL/min. Renal vascular resistance was drastically increased between ANG II+AT1-AA versus NP rats (18.4±2.91 versus 6.4±0.77 mm Hg/mL per minute). Isoprostane excretion was increased by 3.5-fold in ANG II+AT1-AA versus NP (1160±321 versus 323±52 pg/mL). In conclusion, ANG II and AT1-AA together significantly decrease glomerular filtration rate by 37% and renal blood flow by 50% and caused a 3-fold increase in renal vascular resistance and isoprostane levels versus NP rats. These data indicate the importance of AT1-AAs to enhance ANG II–induced renal vasoconstriction and reduce renal function as mechanisms to cause hypertension as observed during preeclampsia.